Determinan Keputusan Penggunaan Asuransi Pembiayaan Syariah di Perbankan Syariah - Wahyudin Rahman; Nur Fatwa (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2022)
The need for sharia insurance protection for Islamic banking financing products creates competition between Sharia Insurance Companies. Determining the marketing strategy demands the right tools, has limits and is measurable. One such tool is through the marketing mix. This study investigates the effect of product, price, promotion, people and process on the decision to use Sharia Financing Insurance products by Person in Charge (PIC) Sharia Banking. The study used a descriptive quantitative approach through multiple regression analysis, coefficient of determination, t test and f test with SPSS software. The results of this study indicate that the entire marketing mix has a direct correlation and am significant influence on usage decisions. The most dominant process variable affects with a coefficient of 0.760. The value of the coefficient of determination (R2) is 0.69, meaning that all of the derivative variables of the positioning strategy have a joint contribution of 69% to the use decision variable and 31% are influenced by other variables outside of this study.